Estimation of biomechanical parameters and propulsive efficiency of flat-water kayak single (K1) at race pace - Rottenbacher, C.; Mimmi, G.; Ramponi, A. (2011)
Flat-water Kayaking is an Olympic discipline in which the boats race are held on calm water in separate lanes delineated with ropes and buoys over the distance of 500 m and 1000 m. A new Sprint 200 m race will make its Olympic debut at London 2012. Few are the experimental data in literature on this particular type of race in which the athlete exerts his maximum effort on a very short distance. This paper presents the analysis of the paddling performance of elite athletes in single K1 training session keeping up a typical stroke race cadence (over 100 spm). In order to reproduce the regatta conditions the tests were performed at Idroscalo water basin (Milan, Italy) with kayaker at the top of the training preparation. The on purpose experimental device, successfully tried out in previous on-water kayaking and canoeing researches was integrated with cardiopulmonary testing portable system. By means of experimental acquisitions including stroke forces, estimated position of the blade propulsion centre (EPPC), boat speed and the movements around the three main axes of the hull it is possible to evaluate the athletes performance during the different phases of the race. Particular attention was devoted to refine the efficiency of stroke through the analysis of the exertion of the force in the active part of paddling (drive phase) related to the metabolic cost of the stroke cycle. The main goal of the research was to implement a low cost stand-alone instrumentation and acquisition system for the on-the-water measurement of biomechanical and dynamical parameters during race paddling of elite athletes to quantify performance and improve technique.